Drought Exposed Burkholderia seminalis JRBHU6 Exhibits Antimicrobial Potential Through Pyrazine-1,4-Dione Derivatives Targeting Multiple Bacterial and Fungal Proteins - Prasad, Jay Kishor; Pandey, Priyanka; Anand, Richa; Raghuwanshi, Richa (Frontiers in Microbiology, 2021)
The present study was aimed to explore the antimicrobial potentials of soil bacteria, identify the bioactive compounds and their likely targets through in silico studies. A total fifty-three bacterial isolates were screened for their antimicrobial activity of which Burkholderia seminalis JRBHU6 strain showed the highest potential. Burkholderia seminalis JRBHU6 was found to be positive for both chitinase and cellulose activities and showed strong antifungal activity against the fungal strains viz; Fusarium oxysporum, Aspergillus niger, Microsporum gypseum, Trichophyton mentagrophytes and Trichoderma harzianum. On testing its antibacterial activity, maximum zone of inhibition was observed against multi-drug resistant Staphylococcus aureus (22.4 mm). The crude extract of Burkholderia seminalis JRBHU6 was purified in different solvents viz; ethyl acetate, acetone, methanol and ethanol. As the methanolic crude extract showed the best activity hence, compounds in the methanolic extract were purified by thin layer chromatography (TLC) and high-performance liquid chromatography (HPLC). Based on spectral data, including GC-MS, FTIR spectroscopy and proton nuclear magnetic resonance (1H NMR), the isolated compound was identified as C7H10O2N2 (pyrrolo[1,2-a]pyrazine-1,4-dione,hexahydro) which targeted chitinase B proteins. An additional compound pyrrolo[1,2-a]pyrazine-1,4-dione, hexahydro-3(2-methylpropyl) revealed in GCMS on molecular docking was found to be multitargeting in nature and is reported for the first time through this study.